Pelayanan Kesehatan dalam Pembangunan Kesejahteraan Sosial di Kecamatan Gandus Kota Palembang - Pusnita, Indah; Wagisri, Wagisri; Berlian, Ong; Marleni, Marleni (Jurnal Publisitas, 2023)
This study discusses how public services provide social welfare to the community. In the study of public service analysis for the social welfare of the community related to local government policies with minimum service standards originating from central policy. This study aims to describe how public services for community social welfare in Gandus District, Palembang City can run well according to the wishes of the local community. This study uses qualitative methods with data collection techniques of observation, interviews, and literature studies. The informants in this study were 13 (thirteen) people, and the sample was taken using the Snowball Sample. The results of the study found that public services related to policies in social welfare services for the community have been going well, this is strengthened by the activities carried out by the Government as much as possible in realizing a good service as a whole for the benefit of society.